Evaluation of Motor Boat Passenger Safety Equipment to Support Ecotourism at Bukit Cinta Pier, Rawa Pening Lake, Semarang Regency, Central Java Province - Susanto, Novi Tri; Agustina, Hera; Atika, Aulia Ika; Saputra, Andena Nugraha (IWTJ : International Water Transport Journal, 2025)
Rawa Pening Lake is a lake located in Semarang Regency, Central Java. With an area of about 2,670 hectares, it occupies the area of Ambarawa, Bawen, Tuntang and Banyubiru Districts. This study discusses safety equipment based on the Regulation of the Director General of Land Transportation Number: KP.3424/AP.402/DRJD/2020. The purpose of this study is to determine the suitability and availability of safety equipment on ships operating at Bukit Cinta Pier using qualitative methods. Based on the results of the research that has been carried out, the condition of the safety equipment on motorboats operating at the Bukit Cinta Pier is not in accordance with existing regulations. This is because there are still ships that have not equipped safety equipment on their ships and there are safety equipment that are not suitable and not in accordance with the number they should be. So it is necessary to add safety equipment to every ship operating at the Bukit Cinta Pier to comply with applicable regulations.